If the Only Tool You Have Is a Hammer, You Will Treat Everything as a Nail: Exploring Why Construction Contractors Monetise Social Value - Watts, Greg; Higham, Anthony (Journal of Leadership, Accountability and Ethics, 2021)
The need to measure and communicate Social Value (SV) is now a priority for many construction contractors. However, this can prove difficult as there exists a conflict at the heart of SV between its subjective nature and the objective way SV is often measured. It needs to be ascertained exactly how contractors measure SV and why, and if monetary metrics are increasingly used for SV measurement, what are the ramifications. This paper aims to understand the motivations and ramifications of contractor SV measurement behaviour, as well as the implications for industry leadership and management.